A review of forecasting techniques for large data sets - Jana Eklund; George Kapetanios (Queen Mary University of London, Department of Economics, 2008)
This paper provides a review which focuses on forecasting using statistical/econometric methods designed for dealing with large data sets.
Keywords: C22; C53; E37; E47; 330; Macroeconomic forecasting; Factor models; Forecast combination; Principal components; Prognoseverfahren